The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1152/ajpheart.00437.2016
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and the development of endothelial dysfunction

Abstract: The vascular endothelium plays a critical role in cardiovascular homeostasis, and thus identifying the underlying causes of endothelial dysfunction has important clinical implications. In this regard, the endoplasmic reticulum (ER) has recently emerged as an important regulator of metabolic processes. Dysfunction within the ER, broadly termed ER stress, evokes the unfolded protein response (UPR), an adaptive pathway that aims to restore ER homeostasis. Although the UPR is the first line of defense against ER s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 154 publications
0
78
0
Order By: Relevance
“…OS was suggested to drive this process through impairment of cellular organelle functions and structure (Table ). In particular, endoplasmic reticulum stress and mitochondrial destruction in vascular and immune cells contribute to atherosclerotic plaque progression by modulating cell apoptosis and lipid peroxidation (Battson, Lee, & Gentile, ; Yang et al, ). Hypercholesterolemia has also been shown to exert direct and indirect effects on myocardial function characterized by impaired cardiac performance and contractile dysfunction.…”
Section: Os and Atheroprogression In Hypercholesterolemiamentioning
confidence: 99%
“…OS was suggested to drive this process through impairment of cellular organelle functions and structure (Table ). In particular, endoplasmic reticulum stress and mitochondrial destruction in vascular and immune cells contribute to atherosclerotic plaque progression by modulating cell apoptosis and lipid peroxidation (Battson, Lee, & Gentile, ; Yang et al, ). Hypercholesterolemia has also been shown to exert direct and indirect effects on myocardial function characterized by impaired cardiac performance and contractile dysfunction.…”
Section: Os and Atheroprogression In Hypercholesterolemiamentioning
confidence: 99%
“…The ER is a large, membrane‐enclosed cellular compartment, critical to the physiologic regulation of many cellular processes, including protein folding, lipid biosynthesis and redox homeostasis 9, 10, 11. Under physiologic conditions, the ER's protein load and folding capacity are in balance; however, ER overload produces an accumulation of misfolded proteins in the ER, leading to the activation of the unfolded protein response (UPR), a process that is known as ER stress 12.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Although the original activation of the UPR can protect the cell against these adverse situations, sustained or excessive UPR is harmful and contributes to cell apoptosis. 7 Accumulation of unfolded proteins within the ER lumen can simultaneously lead to the overexpression of glucose-regulated protein 78 (GRP78/BiP) and C/EBP homologous protein (CHOP), and activate the caspase-12, a crucial protein related to cell apoptosis induced by ER stress. 8 Recent studies have revealed that ER stressinduced apoptosis plays an important role in the pathogenesis and development of many diseases.…”
Section: Introductionmentioning
confidence: 99%